2011
DOI: 10.1007/s00775-011-0840-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the metal center and linker on the intracellular distribution and biological activity of organometal–peptide conjugates

Abstract: Organometallic complexes conjugated to cell-penetrating peptides (CPPs) are promising systems for diagnostic imaging and therapeutic applications in human medicine. Recently, we reported on the synthesis of cymantrene(CpMn(CO)(3))-CPP conjugates with biological activity on different cancer cell lines. However, the precise mechanism of cytotoxicity remained elusive in these studies. To investigate the role of the metal center and the linker between the CpM(CO)(3) moiety and the peptide, a number of derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…We were able to successfully apply sC18 for tumor imaging by conjugation with a metal chelator and a tumor-homing agent, which accumulates in hypoxic tissue [10]. Furthermore, we reported on the delivery of functionalized cyclopentadienyl manganese tricarbonyl (cymantrene) complexes with the help of sC18, which lead to significant induction of cytotoxicity in tumor cells [1113], which was even more pronounced after introduction of an enzymatic cleavage site [12]. However, the aim of the present study was to investigate whether the cytotoxic effect of these organometallic complexes can be further increased by conjugating them to a dimeric variant of sC18, (sC18) 2 , since previous studies demonstrated improvement of the delivery of various kinds of cargo by CPP oligomerization [1415].…”
Section: Introductionmentioning
confidence: 99%
“…We were able to successfully apply sC18 for tumor imaging by conjugation with a metal chelator and a tumor-homing agent, which accumulates in hypoxic tissue [10]. Furthermore, we reported on the delivery of functionalized cyclopentadienyl manganese tricarbonyl (cymantrene) complexes with the help of sC18, which lead to significant induction of cytotoxicity in tumor cells [1113], which was even more pronounced after introduction of an enzymatic cleavage site [12]. However, the aim of the present study was to investigate whether the cytotoxic effect of these organometallic complexes can be further increased by conjugating them to a dimeric variant of sC18, (sC18) 2 , since previous studies demonstrated improvement of the delivery of various kinds of cargo by CPP oligomerization [1415].…”
Section: Introductionmentioning
confidence: 99%
“…Other metal-CO derivatives have been found to be accumulated in specific organelles. 10,11,13,[28][29][30] These various locations show that these probes can be delivered to different cell-compartments depending on their appended moiety, which is a valuable property for imaging applications. 13 Since infrared and luminescence spectroscopies are complementary for bio-detection and bio-imaging, IR-luminescent (L)Re(CO) 3 SCoMPIs are of great potential and their multiple modalities open up wide prospects for cross-correlative studies in biological media.…”
mentioning
confidence: 99%
“…Such a fragmentation was already reported for similar biomolecules. 30 As further confirmation of the identity of the compound, the IR spectrum of 3A showed the vibrations of the CuO at 1927 and 2017 cm −1 . When the Fc precursor B was used as a reaction substrate, lower yields were observed for both the amino acid and the peptide labelling reactions.…”
Section: One-pot Click Reactionmentioning
confidence: 80%